Sowing and Sewing: A Sexagesima Story - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2010)
"Sowing and Sewing: A Sexagesima Story" by Charlotte M. Yonge is a novel written in the late 19th century. The story introduces us to a group of young women, particularly focusing on Amy Lee and her friends, who are grappling with themes of duty, virtue, and personal growth amidst their community responsibilities, particularly in their connection to church and charity work. The narrative weaves in details of their daily lives, including work related to sewing and teaching, reflecting the social expectations and challenges faced by women of that era. The opening of the novel sets the stage with four girls working in a cottage room, each engaged in various sewing tasks while discussing a sermon that has deeply moved them. It showcases the profound impact of spiritual teachings on their aspirations to live a more purposeful life, particularly emphasizing the need to be productive members of society and serve others beyond their immediate families. As they respond to their newfound clarity from the sermon, they consider their roles within the church and community, indicating an emerging sense of responsibility, mutual support, and the desire for moral integrity. This establishes an inviting milieu for readers interested in character-driven stories about personal transformation and societal norms of the time. (This is an automatically generated summary.)
Release date is 2010-05-02
E-text prepared by Emmy, Juliet Sutherland, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Christian life -- Fiction; Villages -- Fiction; Young women -- Conduct of life -- Fiction; Church work -- Fiction